2014
DOI: 10.1183/09031936.00080514
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage activation, age and sex effects of immunometabolism in obese asthma

Abstract: Obese asthma is characterised by infiltration of adipose tissue by activated macrophages and mast cells. The aim of this study was to examine the age and sex effects of immunometabolism in obese asthma.Obese and non-obese asthmatic children and adults underwent spirometry, body composition assessment by dual energy X-ray absorptiometry and measurement of serum soluble CD163 (sCD163), tryptase, C-reactive protein (CRP) and other adipocytokines.Plasma CRP ( p<0.01) and leptin ( p<0.01) were elevated in obese ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 39 publications
2
23
1
Order By: Relevance
“…COPD phenotypes and pathogenesis demonstrate sex variation[93, 94]; additionally, biomarker levels and activity may vary between males and females. ET-1 demonstrates sex differences in the cardiovascular system[95] and kidney[96] and sCD163 has been found to be higher in women[97, 98], with possible modulation by sex hormones[99]. These associations require confirmation in a cohort including female participants.…”
Section: Discussionmentioning
confidence: 99%
“…COPD phenotypes and pathogenesis demonstrate sex variation[93, 94]; additionally, biomarker levels and activity may vary between males and females. ET-1 demonstrates sex differences in the cardiovascular system[95] and kidney[96] and sCD163 has been found to be higher in women[97, 98], with possible modulation by sex hormones[99]. These associations require confirmation in a cohort including female participants.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have linked leptin, a pro-inflammatory adipokine, and its related cytokines IL-6 and TNF, with asthma burden in obese individuals, these inflammatory markers are not routinely used in clinical care. Studies have reported elevated CRP among obese asthmatics [43], which correlates with lower pulmonary function [41] and airway hyper-responsiveness [44]. CRP decreases with weight loss and is associated with improved asthma control and quality of life [45].…”
Section: Discussionmentioning
confidence: 99%
“…43 Obesity is known to be associated with inflammatory phenotypes which vary developmentally and with gender. 44 Recently, the novel hypothesis that the airway may be the target of systemic inflammation has been proposed. 45 In a study of two adult cohorts comprising more than 600 patients, asthma outcomes were related to serum IL-6 (a marker of systemic inflammation).…”
Section: Obesitymentioning
confidence: 99%